Plant blindness: A focus on its biological basis - Achurra, Ainara (Frontiers in Education, 2022)
Plant blindness or the inability to notice plants in one’s everyday life is a complex phenomenon in the field of science education. Although plant blindness is well documented in the literature, the underlying factors, whether biological or cultural, are still under research. Here I focus on its biological basis. That is, I review and discuss how plants’ own inherent characteristics cause effects on human visual and cognitive processes. Animals versus plant differences in human attention and memory are also addressed. Grounded on that knowledge, some recommendations for effective practice in plant science education emerge. I conclude that only when we understand human-plant relationships will we know how to enhance teaching and learning about plants.